Managing fungal pathogens of field crops in sustainable agriculture and AgroVariety internet application as a case study - Elżbieta Czembor; Anna Tratwal; Juliusz Pukacki; Marcin Krystek; Jerzy Henryk Czembor (Journal of Plant Protection Research)
Effective management of plant fungal pathogens is crucial for minimizing economic and environmental impacts of crop diseases in agricultural production. It plays a major role in providing healthy and nutritious food, maintaining human and animal well-being, and maintaining an environmental balance in agroecosystems. These goals agree with agroecology and Integrated Pest Management (IPM). Agroecology integrates ecological principles with agriculture and offers a holistic and environmentally friendly approach to fungal disease management. IPM focuses on prevention and protection against pests and diseases, involving environmentally safe agricultural practices, cultivating resistant plant varieties, and promoting agrobiodiversity. The authors aimed to provide a comprehensive and concise overview of the key components of IPM in sustainable agriculture including recent developments in electronic tools helping farmers to make optimal economic and environmental decisions. While maintaining agroecology principles there is a particular focus on the significance of plant resistance to major pathogens, breeding technologies, effective crop management practices, and non-chemical fungal management. Agroecological approaches to fungal plant pathogen management prioritize the long-term health of agricultural ecosystems, contributing to the overall biodiversity and sustainability of farming systems. To illustrate the practical application of these principles, the AgroVariety application (app), developed for farmers, was used to discuss the role of specialized applications in decision-making for environmentally friendly and cost-effective plant production. This tool emphasizes combining different IPM techniques, with specific emphasis on methods that are least harmful to the environment and tailored to control particular pathogens.